(untitled) (Anclajes, 2018)
During 1941, Ricardo Rojas published a series of entries in the newspaper La Nación about the Selk’nam community in Tierra del Fuego, where he was imprisoned for political reasons in 1934. A year later, Losada collected them in Archipelago. Tierra del Fuego. Rojas’s interest in indigenous cultures was a constant that went through his literary and academic production; however, a different attitude is appreciated in this book: Archipelago is presented as a text of denunciation, a descriptive panorama and self-exploration that under the form of direct investigation invokes stories and silenced voices to expose them to the reading of the aristocratic classes. The exile of Rojas in Ushuaia allowed him to investigate some relevant aspects of the national configuration: the self and the other, the limits of the nation and discourse, the death of languages, the linguistic imposition and its consequences.